ANALISIS KINERJA KEUANGAN KOTA MAGELANG PERIODE 2016 – 2021 PENILAIAN KINERJA BERDASARKAN RASIO KEUANGAN - Annisa Nur Afifah; Ilyas Febriyan; Risma Wira Bharata (Politeknik Negeri Ambon, 2023)
This study aims to examine the financial performance of the local government of Magelnag City for the 2016-2021 fiscal year period. This calculation is carried out using financial ratios which include the regional independence ratio, effectiveness ratio, efficiency ratio and revenue growth analysis. This research uses a quantitative descriptive method with ratio analysis. The secondary data used in this analysis is the Magelang City APBD Realization Report for the period 2016-2021. Based on the results of the study, the level of independence of Magelang City for the 2016-2021 budget period is in the good category, the effectiveness ratio shows very effective, the efficiency ratio shows less efficient performance, while for revenue growth analysis for the 2016-2021 budget period shows fiscal year instability. The local government of Magelang city is expected to be able to accelerate revenue growth by implementing regional financial management properly, increasing regional economic potential and resource quality.